2013
DOI: 10.1177/1941738113495788
|View full text |Cite
|
Sign up to set email alerts
|

Return-to-Sport and Performance After Anterior Cruciate Ligament Reconstruction in National Basketball Association Players

Abstract: Background:Anterior cruciate ligament (ACL) rupture is a significant injury in National Basketball Association (NBA) players.Hypotheses:NBA players undergoing ACL reconstruction (ACLR) have high rates of return to sport (RTS), with RTS the season following surgery, no difference in performance between pre- and postsurgery, and no difference in RTS rate or performance between cases (ACLR) and controls (no ACL tear).Study Design:Case-control.Methods:NBA players undergoing ACLR were evaluated. Matched controls fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
193
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(201 citation statements)
references
References 11 publications
3
193
3
2
Order By: Relevance
“…Seven of these studies measured overall athletic performance using the following: the number of competition medals won by alpine skiers36 and freestyle skiers and snowboarders,24 International Ski Federation (FIS) rankings and points for alpine skiers,36 the number of All-Star team selections for National Basketball Association (NBA)27 and National Hockey League (NHL)37 players and formulated ratings for players in the NBA18 and the National Football League (NFL) 19 38. Eight studies measured performance with various individual statistics, including games played per season,18 22 23 25 27 32 37 38 touchdown passes made by NFL quarterbacks,38 goals scored by soccer23 and ice hockey players,22 37 home runs scored by baseball players25 and shooting percentages among basketball players 18 27 32.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of these studies measured overall athletic performance using the following: the number of competition medals won by alpine skiers36 and freestyle skiers and snowboarders,24 International Ski Federation (FIS) rankings and points for alpine skiers,36 the number of All-Star team selections for National Basketball Association (NBA)27 and National Hockey League (NHL)37 players and formulated ratings for players in the NBA18 and the National Football League (NFL) 19 38. Eight studies measured performance with various individual statistics, including games played per season,18 22 23 25 27 32 37 38 touchdown passes made by NFL quarterbacks,38 goals scored by soccer23 and ice hockey players,22 37 home runs scored by baseball players25 and shooting percentages among basketball players 18 27 32.…”
Section: Resultsmentioning
confidence: 99%
“…The three studies of elite basketball players each reported that players’ postsurgery performance deteriorated compared with preinjury performance on measures including player efficiency rating,18 number of All-Star selections,27 games played per season,18 27 shooting percentage,18 27 32 points and rebounds per game27 and steals per game 32. However, elite basketball players’ performance did not decline significantly compared with those of matched controls,18 32 except Harris et al 27 reported that players returning from ACL reconstruction played fewer games per season.…”
Section: Resultsmentioning
confidence: 99%
“…At the elite level, any decrement in athletic performance can have significant ramifications for players, coaches, and organizations. Ample literature exists regarding the effects of various orthopedic injuries on NBA player performance [8][9][10][11][12]; however, research examining the effect of concussion on NBA player performance is nonexistent. SRCs are well known to adversely affect various neurocognitive functions including attention, reaction time, and processing speed, as well as the domain of postural stability (balance) [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…Mediante este estudio se ha comprobado que la realización de fortalecimiento muscular, junto con ejercicios isométricos, ejercicios en cadena cinética cerrada y propiocepción; favorecen la recuperación de la lesión que conlleva una reducción del tiempo de retorno a la actividad física del individuo (25). Además, el paciente.…”
Section: Discussionunclassified